Features of schizophrenia following premorbid eating disorders. (August 2019) - Malaspina, Dolores; Walsh-Messinger, Julie; Brunner, Anna; Rahman, Nadia; Corcoran, Cheryl; Kimhy, David; Goetz, Raymond R.; Goldman, Sarah Bellovin
Highlights: Ten percent of schizophrenia cases in a large case series met criteria for premorbid eating disorders (ED). They had more severe psychotic and disorganization symptoms but similar functional impairments and negative symptoms as other cases, both during treatment and when medication free. ED cases had significantly better cognition than other cases, but evidenced lower nonverbal than verbal intelligence. Cases with premorbid ED may constitute a distinct subtype of schizophrenia. Premorbid eating disorders should be considered as a feature for psychosis risk in prodromal schizophrenia. Abstract: Objective: Eating disorders (ED) and schizophrenia are frequently comorbid and schizophrenia shares genetic susceptibility with anorexia. Many factors associated with schizophrenia can disrupt eating, but ED can present years before schizophrenia. If premorbid ED distinguishes a particular subtype of schizophrenia, then phenotypic features may differ between schizophrenia cases with and without premorbid ED. Method: This secondary analysis used data from an inpatient schizophrenia research study that comprehensively assessed life course psychiatric disorders (DIGS interview), intelligence (WAIS), global assessments of function (GAF) and assessed symptoms during medication-free and fixed dose neuroleptic phases (PANSS). Results: Premorbid ED was identified in 27 of the 288 schizophrenia cases (9.4%). This group had more females than the group without premorbid ED (74.1% vs. 30%); premorbid ED was 5-fold more common in female than male cases (χ 2 (17.9, P < .0001). Only the premorbid ED group had gustatory hallucinations. They also demonstrated significantly more severe psychotic and disorganization symptoms during medication-free and fixed dose treatment phases, despite similar negative symptoms and GAF scores, as other cases. The premorbid ED group had significantly better cognition overall, but relatively lower nonverbal than verbal intelligence. Discussion: Premorbid ED may define a specific subtype of schizophrenia that is common in females. Their more severe psychotic symptoms and better IQ, despite similarly impaired function and negative symptoms as other cases, suggests a distinct pathophysiology. Premorbid ED should be considered in evaluating risk states for schizophrenia, and as a relevant phenotype for treatment resistant schizophrenia.